2018
DOI: 10.1001/jamaoncol.2017.3989
|View full text |Cite
|
Sign up to set email alerts
|

A Peculiar Adenocarcinoma

Abstract: A man in his 60s presented with a 1-year history of a mild, dry cough. He was otherwise asymptomatic and had no physical limitations. He had never smoked, and results of his physical examination were normal. Results of complete blood cell counts, basic metabolic panel, and liver function tests were all within normal limits. A chest radiograph revealed a 10 × 9-cm lobulated left lower lobe mass. Examination of a biopsy specimen showed a primary adenocarcinoma with an immunohistochemical profile of CDX2 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…( 16 ). The most prevalent distant metastatic sites in patients with advanced stages were lung, bone, liver, distant lymph nodes, and adrenal metastases ( 6 , 20 ), whereas skin and pancreatic metastases were rare ( 21 , 22 ). Feng et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…( 16 ). The most prevalent distant metastatic sites in patients with advanced stages were lung, bone, liver, distant lymph nodes, and adrenal metastases ( 6 , 20 ), whereas skin and pancreatic metastases were rare ( 21 , 22 ). Feng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al. ( 20 ) covered a 60-year-old male patient treated with docetaxel + cisplatin after surgery. Six months later, the disease relapsed, then he received nivolumab, which remained effective for more than 14 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are among the key findings of a recent study published as a research letter in JAMA Oncology that examined trends in functional limitations among US cancer survivors between 1999 and 2018 1 . The study builds on data from a prior study showing that 70% of cancer survivors in 2018 reported some functional limitation—a rate nearly twice that of the general population 2 …”
mentioning
confidence: 85%